2020
DOI: 10.21037/jgo-20-54
|View full text |Cite
|
Sign up to set email alerts
|

Indolent T cell lymphoproliferative disorder of the gastrointestinal tract: an uncommon case with lymph node involvement and the classic Hodgkin’s lymphoma

Abstract: Here we describe an unusual case of an indolent CD8+ T-cell lymphoproliferative disorder in the gastrointestinal tract (ITCLD-GT) accompanied by neck lymph node infiltration and new onset of classic Hodgkin's lymphoma after two years follow-up. Previously, this 42-year-old Asian man suffered from diarrhea and abdominal pain for two years. Intestinal biopsies showed a group of small to intermediatesized lymphocytes which were monomorphic as well as arranged in a nodular pattern with no clear boundary and were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The degree of CD8 + ITLPD-GI involvement varies, but is frequently multifocal; it could affect almost all GI tract segments. In these 29 patients, the small intestine (62.1%), colon (48.3%), stomach (20.7%), oral cavity (13.8%) and esophagus (13.8%) were mostly involved; only ve cases have been reported outside the gastrointestinal tract, including two, two and one that involved the bone marrow,(15, 30) lymph nodes, (29,32) and the uterus. (23) The most common clinical symptoms are chronic abdominal pain (37.9%), diarrhea (48.3%) and weight loss (20.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of CD8 + ITLPD-GI involvement varies, but is frequently multifocal; it could affect almost all GI tract segments. In these 29 patients, the small intestine (62.1%), colon (48.3%), stomach (20.7%), oral cavity (13.8%) and esophagus (13.8%) were mostly involved; only ve cases have been reported outside the gastrointestinal tract, including two, two and one that involved the bone marrow,(15, 30) lymph nodes, (29,32) and the uterus. (23) The most common clinical symptoms are chronic abdominal pain (37.9%), diarrhea (48.3%) and weight loss (20.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several studies have provided insights into the properties of CD8 + ITLPD-GI. (8,11,15,19,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) So far, a literature review revealed 15 articles reporting CD8 + ITLPDGI in 29 patients, including 19 male and 10 female cases, averaging 42 years (range, 15-77 years) old. The degree of CD8 + ITLPD-GI involvement varies, but is frequently multifocal; it could affect almost all GI tract segments.…”
Section: Discussionmentioning
confidence: 99%
“…In these 29 patients, the small intestine (62.1%), colon (48.3%), stomach (20.7%), oral cavity (13.8%) and esophagus (13.8%) were mostly involved. Only five cases have been reported outside the gastrointestinal tract, including two, two and one cases that involved the bone marrow[ 15 , 30 ], lymph nodes[ 29 , 32 ], and the uterus, respectively[ 23 ]. The most common clinical symptoms were chronic abdominal pain (37.9%), diarrhea (48.3%) and weight loss (20.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Among the 29 reported patients with CD8+ ITLPD-GI, the overall prognosis was good. Survival analysis at 6-324 mo of follow-up showed that only 1 patient died after 324 mo[ 30 ], and only 4 showed transformation[ 19 , 26 , 30 , 32 ]. Sharma et al [ 19 ] reported a CD8+ ITLPD-GI case who further developed systemic ALK- anaplastic large cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…ITLPD-GI is a newly defined provisional entity in the revised 4th edition of the WHO classification [ 5 ]. The literature on low-grade T-cell LPD of the GI tract has been limited to small case series and case reports [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. The age distribution of patients is 15–77 years, and it is slightly more common in men than in women [ 84 , 85 , 87 , 90 , 100 ].…”
Section: Indolent T-cell Lymphoproliferative Disorder Of the Gastrointestinal Tract (Itlpd-gi)mentioning
confidence: 99%